Designing an Ethics Course in an Engineering Master using narrative and ANT - Figueiredo, Jose (Archives of Business Research, 2020)
Engineers need to understand and measure the consequences of their actions, in terms of value for the organization, community, and in terms of sustainability. This simple formulation, however, hides a background of complexity that is not easy to identify. Students can develop an ethical consciousness, but their awareness is usually fragmented, that is, it is not deeply internalized. And one cannot have ethical thinking only in certain circumstances, looking only into some aspects and not the whole. What we are trying to achieve with this paper is to raise awareness to make ethical reasoning possible, to make ethics a whole system in engineering life. To guide us we use three aligned methodological approaches: Actor Network Theory (to formulate our settings and problematize goals), Bologna framework (to visit the roots of an “innovative” learning breakdown), and finally narrative (as storytelling, a constructivist way to reason and explore our reflections).